Bibliometric analysis of case-control studies on the association between HLA alleles and multiple sclerosis in adults - Maer, Enola; Hubacher, Marjorie Maya; Popa, Livia Livint; Fodor, Dana Marieta; Chereches, Razvan Mircea; Muresanu, Dafin F.; Vacaras, Vitalie; Chiriac, Maria; Matei, Horea Vladi; Draghici, Nicu Catalin; Florea, Adrian (Frontiers in Genetics, 2025)
BackgroundMultiple sclerosis (MS) is a complex autoimmune disease that affects the central nervous system (CNS) with genetic and environmental factors playing a significant role in its development and progression. One of the most important genetic factors associated with MS is the HLA gene complex. The relationship between HLA and MS has been the subject of numerous studies, but no bibliometric analysis of this research has been reported to date. Therefore, this study aimed to provide a comprehensive overview of the publication output, citation impact, collaboration patterns, and research topics related to HLA and MS.MethodsA bibliometric analysis of 488 studies published between 1988 and 2023 was conducted using RStudio, Tableau and VOSviewer software.ResultsThe results indicated an increasing trend in the number of publications and citations over time, with the highest productivity and impact coming from researchers in the United States, Italy and Sweden. The analysis also revealed collaboration networks among researchers and institutions, with the most common research topics being the association of HLA alleles with MS susceptibility, disease course, and treatment response. This study’s limitations stem from the inherent biases associated with bibliometric analysis, including database and coverage bias, citation bias, and biases related to accessibility and open access. Additionally, the exclusion of non-English language articles represents a further limitation.ConclusionOverall, this bibliometric analysis provides valuable insight into the research landscape of HLA and MS, highlighting the areas that have received the most attention and identifying potential avenues for future research.